An investigation into the differences in outcomes between the use of the Limbal technique and the Scleral technique in Cataract Surgery at the St John Eye Hospital - Mudau, Lerato Patience (My University, 2020)
Purpose: The aim of this study was to investigate the differences in outcomes between the use of the limbal technique and the scleral technique in cataract surgery at St John Eye Hospital. Methods: Retrospective record review (clinical audit) of outcomes in patients who had undergone either of the two cataract surgery techniques at St John Eye hospital between the dates of 1 January 2011 to 31 December 2015. The Scleral tunnel technique patients were 67 and the Limbal technique patients were 22 in number. Patients’ data parameters such as uncorrected and corrected visual acuity were recorded at pre-operation, 1 week, 1 month, and 3 months after surgery as well as post-operative complications and surgically induced astigmatism. Statistical analysis was done on these parameters. Results: Both groups achieved an improvement in the mean visual acuity. In the Scleral group, the improvement was from an average visual acuity of 0.66 (±0.29 SD) at week 1 to an average Best Corrected Visual Acuity (BCVA) of 0.17 (±0.33 SD) at 3 months. In the Limbal group, the improvement was from an average visual acuity of 0.89 (±0.20 SD) at week 1 to an average BCVA of 0.34 (±0.21 SD) at 3 months. There was also no statistically significant difference in the improvement of visual acuity with the two techniques. There was a statistically significant difference between the outcomes of the Limbal and Scleral techniques when it comes to surgically induced astigmatism (p < 0.05). Higher astigmatism was observed in the Limbal technique group than in the Scleral technique group induced astigmatism cases. Only 23% of the Scleral induced astigmatism cases required correction (i.e. had high astigmatism with k value >1.5) while 65% required Removal of Sutures (ROS) to correct the astigmatism for the Limbal technique cases. Both groups achieved good visual outcome with minor complications, 58% of which were from the Scleral technique while 42% were from the Limbal technique. Common complications were corneal oedema, pc tear, correctopic pupil, Iris prolapse and corneal haze. There was no statistically significant difference in the complication rate between the groups (p >0.05). Conclusions: Despite the shortcomings, this study has shown that in cataract extraction surgery conducted at St John’s Eye Hospital, both the Scleral and the Limbal techniques achieved good and statistically similar (p>0.05) visual outcomes, with low complication rates. However, the likelihood of corneal oedema complication among the most prevalent encountered in the data, is more with the Scleral technique than the Limbal technique (p <0.05), possibly associated with increased endothelial cell loss due to surgical manoeuvres in the anterior chamber. The major limitation of this study is the fact that there were missing or incomplete records for the study. The results of this study may therefore not be generalisable to St John’s Eye Hospital’s patient population
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Medicine in the branch of Ophthalmology, 2020